2020
DOI: 10.1016/s2589-7500(20)30185-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of artificial intelligence-based triaging of breast cancer screening mammograms on cancer detection and radiologist workload: a retrospective simulation study

Abstract: Background We examined the potential change in cancer detection when using an artificial intelligence (AI) cancer-detection software to triage certain screening examinations into a no radiologist work stream, and then after regular radiologist assessment of the remainder, triage certain screening examinations into an enhanced assessment work stream. The purpose of enhanced assessment was to simulate selection of women for more sensitive screening promoting early detection of cancers that would otherwise be dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
157
1
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(170 citation statements)
references
References 24 publications
4
157
1
8
Order By: Relevance
“…Al respecto, detallamos como la IA aporta grandes beneficios mediante reconocimiento automático de patrones complejos de imágenes radiológicas, con evaluaciones cuantitativas derivadas de cualidades independientemente de la ubicación anatómica o patología involucrada, según lo establecido por Hosny et al, (2018). Adicionalmente, Dembrower et al, (2020) destacan su exactitud diagnóstica que supera la perceptibilidad de la visión humana, tomando esta ventaja en la detección del cáncer mamario; mientras Curioso & Brunette, (2020) presentan un algoritmo de aprendizaje profundo de análisis remoto de rayos X (eRx) que contribuye con el diagnóstico oportuno de tuberculosis. En diagnóstico microscópico, los trabajos de Torres et al, (2018) sobre algoritmos de aprendizaje automático nos revelan que su rendimiento diagnóstico, es equiparable a la microscopía óptica en el reconocimiento de parásitos maláricos en humanos, como P. falciparum y P. vivax.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Al respecto, detallamos como la IA aporta grandes beneficios mediante reconocimiento automático de patrones complejos de imágenes radiológicas, con evaluaciones cuantitativas derivadas de cualidades independientemente de la ubicación anatómica o patología involucrada, según lo establecido por Hosny et al, (2018). Adicionalmente, Dembrower et al, (2020) destacan su exactitud diagnóstica que supera la perceptibilidad de la visión humana, tomando esta ventaja en la detección del cáncer mamario; mientras Curioso & Brunette, (2020) presentan un algoritmo de aprendizaje profundo de análisis remoto de rayos X (eRx) que contribuye con el diagnóstico oportuno de tuberculosis. En diagnóstico microscópico, los trabajos de Torres et al, (2018) sobre algoritmos de aprendizaje automático nos revelan que su rendimiento diagnóstico, es equiparable a la microscopía óptica en el reconocimiento de parásitos maláricos en humanos, como P. falciparum y P. vivax.…”
Section: Discussionunclassified
“…Aplicando el anterior concepto, Dembrower et al, (2020) estudiaron una población de 7.364 mujeres que asistieron a dos rondas de detección consecutivas, de las que 547 fueron previamente diagnosticadas con cáncer de mama y 6817 correspondían a resultados normales, mediante un software de detección de cáncer clasificando exámenes en un flujo de trabajo sin radiólogo; resultando en una detección adicional de cáncer del 2,6% (1,1 a 5,4%, IC = 95%) que se habían pasado por alto en los análisis humanos, siendo una potencial herramienta preventiva al detectar una proporción sustancial de cánceres que de otro modo se diagnosticarían más tarde.…”
Section: Figura 5 Intencionalidad Del Uso De Ia En Enfermedades Crónicas A) Frecuencias Absolutas B) Porcentajes Relativosunclassified
“…The potential of AI for workflow optimization is also being explored in use cases, but this has not been put into clinical practice. For mammography screening, for example, studies have been performed to simulate an alternative workflow in which an AI risk score determines the number of radiology reads (none, single or double), reducing the total amount of reading time (level 3) [14,15]. For lung nodule detection on CT, it has been proposed to empower technicians with AI to leave only some of the workload to the radiologists (level 3) [16].…”
Section: More Efficient Workflowmentioning
confidence: 99%
“…Furthermore, these systems have been proposed as an option for independent reading. Along these lines, a recent report by Dembrower et al concluded that the use of AI CAD systems for triage mammograms without radiologist supervision could potentially reduce radiologists' workload by more than half and also pre-emptively detect a substantial proportion of cancers, which would otherwise be diagnosed later (16). In the short-term, the most realistic scenario regarding the use of AI CAD tools for breast screening diagnosis will probably be focused on their use as an independent second reader in order to reduce the radiologist's workload (17).…”
mentioning
confidence: 99%